Analysis of Mathematics National Exam Questions based on TIMSS Taxonomy - Nur Colis (Program Studi Tadris Matematika IAIN Salatiga, 2021)
The purpose of this research was to find out the spread out content and cognitive dimension of the question of Mathematics National Exam for Junior High School (SMP) / Islamic Junior High School (MTs) in the school year of 2005/2006-2018/2019 and find out the suitability question of Mathematics Final Exam in Junior High School based on government guidelines and TIMSS taxonomy. This type of research is a qualitative approach. This research use collection data with document analysis. Data analysis techniques consist of data reduction, data display, and verification. The research subjects were in the form of 14 SMP / MTs national mathematics exam texts from the 2005/2006 to 2018/2019 academic year. The indicators of content dimensions and cognitive dimensions used are based on the TIMSS taxonomy. Checking the validity of the data, the researcher uses a triangulation by an expert through Online FGD (Focus Group Discussion).The research result as follows: 1. An analysis a question of Mathematics Final Exam in Junior High School in the school year of 2005/2006-2018/2019 based on a taxonomy TIMSS obtain results that percentage spread of content and cognitive dimension still not appropriate yet with TIMSS Assessment Framework. At the content dimension, the spread of a question dominated by geometry domain while data and probability have spread of a question very few. Then, algebra and number domain pretty close proportion which have been specified by TIMSS. 2. the question of Mathematics Final Exam in Junior High School to the scope of material which set by the government was not given percentage distribution of materials obviously while cognitive level from government obtains a result that different with findings result in the researcher based on TIMSS taxonomy because there is different definition at government cognitive level from with TIMSS cognitive domain. There is a question that includes an application in government cognitive level however it includes knowing domain based on TIMSS taxonomy. Suitability a question of Final Exam from the school year of 2005/2006 till 2018/2019 indicate there are percentages increase from year to year close appropriate to proportion TIMSS Assessment Framework. It shows the percentage each other domain close proportion TIMSS in content and cognitive dimension.